2016
DOI: 10.1002/admi.201600512
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Electron Transport and Memristive Switching in Nanoscale Au/WOx/W Multijunctions Based on Anodically Oxidized Al/W Metal Layers

Abstract: size effect. [1][2][3] Eventual functionalization of WO x nanostructures through modifying the surface and interfacial properties by combining, doping, or decorating the pure oxide with other nanomaterials creates additional metal/semiconductor or semiconductor/semiconductor interfaces and grain boundaries capable of further infl uencing the sensing, electrical, optical, and opto-electronic properties or even introducing novel unique functionalities. [4][5][6] Contrarily to WO x nanostructures with no directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The resistance change is a result of ion motion, similar to that observed in biological synapses and neurons. Their unique features make memristors a natural choice for the building blocks of neural networks with a broad spectrum of applications such as computer vision, speech recognition, autonomous vehicles, robotics, and medicine. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The resistance change is a result of ion motion, similar to that observed in biological synapses and neurons. Their unique features make memristors a natural choice for the building blocks of neural networks with a broad spectrum of applications such as computer vision, speech recognition, autonomous vehicles, robotics, and medicine. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In the case of anodizing of metallic alloys, resulting oxide will be a mixed oxide in which the atomic ratio between partner metals can be different with respect to the underlying alloys depending on transport numbers of involved cations. To date, there are several papers in which porous anodic aluminum oxide is used as a matrix for the fabrication of ReRAMs [30][31][32][33] or anodic nanostructured oxides are used as solid electrolytes, [34][35][36][37][38] but only few papers discuss on ReRAMs devices with barriertype anodic oxides however not showing some particular promises. [39][40][41][42] Here we demonstrate Ta/Ta 2 O 5 /Pt system with electrochemically grown Ta Increasing the voltage over + 3 V leads to a formation of filament i.e.…”
mentioning
confidence: 99%
“…It was found that these metal (Au, Ag, Pt) NPs can serve as electron traps to boost separation of photoinduced electrons and holes leading to markedly enhanced photoactivities. Apart from LbL assembly approach, other synthetic strategy was developed to achieve decoration of Au NPs on the anodized tungsten-oxide (Au/WO x ) nanostructures [132].…”
Section: Nobel Metal Depositionmentioning
confidence: 99%